Production of organic products in agriculture and requirements for it - Khatamova Khurshida Ochildievna (Genius Journals, 2023)
The article the emergence of new concepts and requirements in the sustainable development of the world economy cannot fail to affect such a field as agriculture, which is directly related to nature, but also causes great ecological damage to it.
Keywords: Organic; world economy